DIAGNOSTIC ASSESSMENT BASED ON QUIZIZZ ON THE TOPIC OF ENVIRONMENTAL CHANGE - Arum, Dewi sekar; Fawwaz, Hana Fatiya; Ristanto, Rizhal Hendi; Isfaeni, Hanum; Az-Zahra , Rania (Universitas Lancang Kuning, 2024)
Diagnostic assessments are divided into non-cognitive and cognitive. Cognitive diagnostic assessment is important to know how to analyze the basic abilities of students in the topic of a subject and in order to serve as a reference for teachers in designing learning according to the needs of students. The purpose of the research is to facilitate teachers in designing learning that is aligned with the needs of students, especially on the material of environmental change. The method used in this study is research and development using the ADDIE approach. The development of interactive web-based cognitive diagnostic assessment instruments such as Quizizz on class X environmental change material is effective based on the results of validity (34/35 valid questions), reliability (0,884) and expert testing (86%; very feasible). This cognitive diagnostic assessment test can be developed within a certain period of time to be able to adjust to the needs of students periodically.